Incidence of adverse events in Sweden during 2013–2016: a cohort study describing the implementation of a national trigger tool. Issue 3 (30th March 2018) - Nilsson, Lena; Borgstedt-Risberg, Madeleine; Soop, Michael; Nylén, Urban; Ålenius, Carina; Rutberg, Hans
Abstract : Objectives: To describe the implementation of a trigger tool in Sweden and present the national incidence of adverse events (AEs) over a 4-year period during which an ongoing national patient safety initiative was terminated. Design: Cohort study using retrospective record review based on a trigger tool methodology. Setting and participants: Patients ≥18 years admitted to all somatic acute care hospitals in Sweden from 2013 to 2016 were randomised into the study. Primary and secondary outcome measures: Primary outcome measure was the incidence of AEs, and secondary measures were type of injury, severity of harm, preventability of AEs, estimated healthcare cost of AEs and incidence of AEs in patients cared for in another type of unit than the one specialised for their medical needs ('off-site'). Results: In a review of 64 917 admissions, the average AE rates in 2014 (11.6%), 2015 (10.9%) and 2016 (11.4%) were significantly lower than in 2013 (13.1%). The decrease in the AE rates was seen in different age groups, in both genders and for preventable and non-preventable AEs. The decrease comprised only the least severe AEs. The types of AEs that decreased were hospital-acquired infections, urinary bladder distention and compromised vital signs. Patients cared for 'off-site' had 84% more preventable AEs than patients cared for in the appropriate units. The cost of increased length of stay associated with preventable AEs corresponded to 13%–14% of the total cost of somatic hospital care in Sweden. Conclusions: The rate of AEs in Swedish somatic hospitals has decreased from 2013 to 2016. Retrospective record review can be used to monitor patient safety over time, to assess the effects of national patient safety interventions and analyse challenges to patient safety such as the increasing care of patients 'off-site'. It was found that the economic burden of preventable AEs is high.